Medical Student Involvement in a Human Rights Program: Impact on Student Development and Career Vision - Stephanie M. Schonholz; Madison C. Edens; Axel Yannick Epié; Sophie Karwoska Kligler; Kim A. Baranowski; Elizabeth K. Singer (Ubiquity Press, 2020)
Background: There is consensus among many medical school deans that exposure to human rights is a necessary component of physician training [7, 8], however little is known about the impact of engagement in human rights programs on students' personal and professional development [15-28]. Objective: This study aimed to examine medical students' experiences in the Mount Sinai Human Rights Program (MSHRP), their motivations for involvement, and the possible influence of engagement on their professional identities, personal growth, and career choices. Methods: Through semi-structured interviews, this qualitative study gathered the experiences of 15 fourth year and recently graduated medical students who participated in the comprehensive training, research, and direct service opportunities provided by the program. Responses were coded using a content analysis approach. Findings: The results of this research highlight the motivations behind students' involvement in a medical human rights program, as well as the challenges they experienced engaging with this work. The study captured students' perceptions of the role of the program on their personal growth, clinical skills, and career vision. Nearly all the students interviewed indicated they developed important, clinically applicable skills that enhanced their traditional medical education. Students indicated that their participation directly influenced their professional identities and future career directions by reinforcing previous interests in human rights and social justice work, impacting medical specialty and residency program selections and fostering commitment to working with immigrant populations. Conclusions: The results of this study indicate that longitudinal involvement with the MSHRP contributed to the acquisition of important clinical skills that were not otherwise attained in students' early medical education. Findings suggest that there is significant opportunity for clinical and leadership development outside the traditional preclinical and clinical setting, and that exposure to human rights education shapes students' professional identities and career paths. Finally, the findings highlight the essential role of human rights and social justice in medical education.